Ability of stem and progenitor cells in the dental pulp to form hard tissue. Issue 3 (August 2015) - Hosoya, Akihiro; Nakamura, Hiroaki
Summary: Dental pulp has an important ability to form mineralized hard tissue in response to a variety of external stimuli. The formation of mineralized tissue within the pulp cavity has been widely examined in both clinical and animal studies. Despite these studies focusing on the phenomena of reparative dentin and dentin bridge formation, the mechanisms of their induction remain unknown. Recently, several morphological studies revealed that the source of cells for hard tissue formation is the dental pulp itself, even after pulp injury. This finding indicates that the dental pulp tissue contains undifferentiated cells participating in dentin and pulp regeneration. Additionally, stem and progenitor cells isolated from the dental pulp were found to differentiate into odontoblasts as well as osteoblasts. This review presents current evidences for the multipotent ability of dental pulp cells and their usefulness in tissue engineering applications as a cell resource.